2021
DOI: 10.1186/s12889-021-11170-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic non-communicable diseases in Ghana: a qualitative study using the chronic care model

Abstract: Background While the burden and mortality from chronic non-communicable diseases (CNCDs) have reached epidemic proportions in sub-Saharan Africa (SSA), decision-makers and individuals still consider CNCDs to be infrequent and, therefore, do not pay the needed attention to their management. We, therefore, explored the practices and challenges associated with the management of CNCDs by patients and health professionals. Methods This was a qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…This observation in the present study, where patients engaged in social activities such as visiting families and friends as well as attending social gathering as a coping mechanism point to the role of families and friends in enabling patients with the chronic non-communicable disease to cope with their conditions. This is consistent with the findings of previous studies where patients suffering from chronic diseases sought social support by talking to families and friends as a way of coping with their conditions [ 25 , 36 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation in the present study, where patients engaged in social activities such as visiting families and friends as well as attending social gathering as a coping mechanism point to the role of families and friends in enabling patients with the chronic non-communicable disease to cope with their conditions. This is consistent with the findings of previous studies where patients suffering from chronic diseases sought social support by talking to families and friends as a way of coping with their conditions [ 25 , 36 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Ethical clearance (Reference number: UHAS-REC A.9 [ 36 ] 20–21) was obtained from the University of Health and Allied Sciences Review Committee and authorization from the hospital before data was collected. Informed consent had been obtained from participants before including them in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In the majority of studies, data was collected from extremely poor rural locations or city slums. Not surprisingly, many research participants reported difficulties in accessing health care, including financial barriers, drug shortages and lack of transport [8][9][10][11][12][13]. Six studies also cited shortages of health-care workers and unfriendly interactions with health-care providers as barriers to accessing health care [11,[14][15][16][17][18].…”
Section: Good Health and Well-beingmentioning
confidence: 99%
“…Ghana and other sub-Saharan African countries are facing a steady increase in the prevalence of diabetes and other NCDs, driven by the increasing incidence of NCD risk factors such as physical inactivity and unhealthy diets. This epidemiological transition is evident in Ghana, where around 43% of deaths are caused by NCDs and the health system is not currently built to tackle this rising burden [ 19 , 20 ]; thus the need to explore approaches that can help in the prevention and management of NCDs is crucial [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%